Mineralocorticoid receptor overactivation-induced remodeling of obese adipose tissue - WEN Runzhi, WANG Li, ZHAO Naiqian (Xin yixue)
Obesity is a chronic disease caused by the long-term interaction of multiple environmental factors on a specific genetic background. Among these factors， the overactivation of mineralocorticoid receptors （MR） plays a significant role in adipose tissue remodeling in obesity. In the obese state， the MR overactivation in adipose tissue can promote adipose tissue differentiation and adipogenesis， and induce adipose tissue inflammation， oxidative stress， adipokine secretion disorders， and insulin resistance. These mechanisms contribute to adipose tissue remodeling in obesity， which is a key determinant of obesity-related metabolic diseases. Moreover， the use of MR antagonists can partially reverse the adipose tissue remodeling in obesity caused by MR overactivation. Therefore， it is of significant importance to clarify the role and mechanisms of MR overactivation in adipose tissue remodeling in obesity.